Способ умножения частоты несущего колебания фазоманипулированных сигналов - Лимаренко, П. В. (Weber, 2010)
The method of PSK signal’s carrier frequency multiplying that saves information phase characteristics in the output signal is offered.
Keywords: фазоманипулированный сигнал